The kissing hand - Penn, Audrey; Harper, Ruth E.; Leak, Nancy M. (New York : Scholastic, 1998)
When Chester the raccoon is reluctant to go to kindergarten for the first time, his mother teaches him a secret way to carry her love with him.
Keywords: Children's stories